Deconstructing the performance of everyday activities: a case in dementia. (8th February 2017) - Giebel, Clarissa M.; Montaldi, Daniela
ABSTRACT: Background: The assessment of everyday functioning in dementia is currently very global and in most cases fails to provide an in-depth overview of specific areas of deficits. Every activity comprises different sub-tasks which may be impaired to different degrees. Performance of some sub-tasks might be maintained and could thus be the foundation for remaining independent for longer. Thus, the objective of this study was to explore the benefits of breaking down everyday activities into sub-tasks. Methods: A total of 183 family carers of people with mild dementia completed the revised Interview for Deteriorations in Daily Living Activities in Dementia 2 (R-IDDD2) rating their relative's everyday functioning. Each of the 20 activities comprised three sub-tasks. Data were analyzed using ANOVA with Bonferroni corrections, and sub-tasks were clustered in relation to different forms of cognition. Results: The majority of activities showed at least one major area of impairment. Sub-tasks could be clustered based on different types of cognition. Several sub-tasks had a focus on memory (forgetting it is time to do the cleaning; forgetting previously known telephone numbers), whereby short-term, long-term, and prospective memory could be distinguished further. Other sub-tasks were clustered into attention (getting more distracted when driving) and executive function (sorting out bills). Conclusions: The R-IDDD2 and its analysis of sub-task performance offers a novel platform to examine impairments comprehensively. This can help both in aiding timelier diagnosis by recognizing subtle deficits, but also in care management planning, whereby family and paid carers should only care for those sub-tasks that are most impaired and thus encourage remaining independent for longer.